PEMBERDAYAAN SISWA SEBAGAI AGEN BUDAYA BANYUWANGI DI SD NEGERI 1 SUMBERBARU - Trianingsih, Rima; Sulastri; Asini (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
Culture is transmitted from one generation to the next generation. To realize the process of cultural transmission, the role of schools as agents of cultural socialization is very vital. Therefore, SD Negeri 1 Sumberbaru is pro-active to realize through student empowerment activities as an agent of Banyuwangi culture. The purpose of this activity is to carry out the transmission of Banyuwangi culture to students as the next generation. Furthermore, students are encouraged to have an active role in the process of socializing Banyuwangi culture in the family, school, and community environment. The service method used in this activity is student empowerment training through various intracurricular, cocurricular and extracurricular activities. The results of all the activities that have been carried out show that students have a good motivation to become agents of Banyuwangi Culture. This is shown by students' self-awareness to learn more Banyuwangi culture and disseminate it through various social media accounts as well as in the family, school and community environment.